Fiscal illusion and the shadow economy: Two sides of the same coin? - Friedrich Schneider; Andreas Buehn; Roberto Dell'Anno (Johannes Kepler University of Linz, Department of Economics, 2013)
This paper presents an empirical analysis of the relationship between fiscal illusion and the shadow economy for 104 countries over the period 1989-2009. We argue that both unobservable phenomena are closely linked to each other, as the creation of a fiscal illusion may be helpful if governments want to control shadow economic activities. Using a MIMIC model with two latent variables we confirm previous findings on the driving forces of the shadow economy and identify the main determinants and indicators of fiscal. Most importantly, we find that fiscal illusion negatively affects the shadow economy: Concealing the real tax burden through fiscal illusion potentially contributes to the government's efforts to repress shadow economic activities.
Keywords: O17; K42; O54; N16; 330; Fiscal illusion; shadow economy; MIMIC model; latent variables; tax burden; tax complexity